PENGARUH UKURAN PERUSAHAAN, PERGANTIAN MANAJEMEN, FINANCIAL DISTRESS, DAN FEE AUDIT TERHADAP AUDITOR SWITCHING - Ilmi Firdatul Afidah; Sumiadji; Triesti Candrawati (Jurnal Kajian Akuntansi dan Auditing, 2023)
This research aims to examine and analyze the effect of company size, management change, financial distress, and audit fees on auditor switching. Objects of this research are companies in the consumer non-cyclical sector which are listed on the Indonesia Stock Exchange for 2017-2021. It is quantitative research using logistic regression analysis to analyze the data. Sample of data were 21 companies which were obtained using purposive sampling method. The dependent variables used in this research are auditor switching, while the independent variables are company size, management change, financial distress, and audit fees. The results simultaneously showed that company size, management change, financial distress, and audit fees have a significant effect on auditor switching. Partially, financial distress and audit fees have a significant effect on auditor switching, while company size and management change have no significant effect on auditor switching. This research concludes that companies experiencing financial distress and the large audit fees potentially conduct auditor switching.